solve it fast it's urgent
Attachments:
![](https://hi-static.z-dn.net/files/d21/d0f2d63fba3941b55fa64a4d7a2ea051.jpg)
Answers
Answered by
1
Answer:
(a) Let p (x) = 5x – 4x2 + 3 …(i)
On putting x = -1 in Eq. (i), we get
p(-1) = 5(-1) -4(-1)2 + 3= - 5 - 4 + 3 = -6
Answered by
1
Answer:
(c) -6
Explanation:
plzz refer to the attachment...
hope this helps you...plzz Mark as BRAINLIEST answer❤
Attachments:
![](https://hi-static.z-dn.net/files/dbf/c83b9a3e99922fd346ebc74b089af116.jpg)
Similar questions